A influência da agilidade mediada pelo uso do método scrum para conversão do conhecimento - Santos, Marcelina Felix dos (2023)
Companies continually seek to position themselves in the face of market competitiveness in an agile and innovative way. In addition to this aspect, they foster knowledge in order to constitute spaces for a holistic and systemic view, which make it possible to see problems quickly, proactively and envision opportunities. Organizational agility is the necessary fuel to respond to changes through efficiency, effectiveness and effectiveness, so that they can compete in a global and highly competitive market. At the beginning of the 21st century, new practices emerged, recognized as Agile Methodologies and these began to be preferred over traditional methods, as they have characteristics that encourage collective work. They are aimed at faster deliveries based on shorter cycles, with potential for knowledge dissemination. Currently, adopting a learning ecosystem in the conversion of knowledge, aligned with the agile SCRUM methodology, is a path pursued by organizations ahead of their time. Therefore, it is configured as a prominent alternative in the conception of flexibility and speed, requirements that the market promotes, both for reasons of adaptability and permanence in the world market. This descriptive research, with a quantitative approach, aims to evaluate, using the SCRUM method, the agility of high teams in a Financial Institution located in the city of Porto Alegre/RS. The research instrument used was a questionnaire applied to the organization's leaders. The content analyzes were elaborated through basic statistical measures to reach the profile of the leaders of the Financial Institution in question. As a result of this research, it is concluded that the SCRUM methodology adds values, being able to generate responsibility, knowledge, trust, continuous learning, agility in responses and deliveries, promotion of multidisciplinarity, interaction and, consequently, dissemination of knowledge among the members of the high team.